FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Yohanna Nainggolan (Politeknik Negeri Ambon, 2022)
This study aims to examine and determine the impact of good corporate governance in terms of independent commissioners, managerial ownership, institutional ownership, and audit committees on the financial performance of property and real estate companies listed on the Indonesia Stock Exchange. This type of research is quantitative. There are 49 property and real estate companies that are the population in this study. The sample selection method is a purposive sampling method, and the samples obtained are from 24 companies. The data used is secondary data, namely quantitative data obtained from the Indonesian stock exchange, and data collection is carried out by downloading the financial statements of each property and real estate company listed on the Indonesia Stock Exchange. Based on the partial test results, it shows that the independent board of commissioners has an effect on financial performance. Meanwhile, managerial ownership, institutional ownership, and the audit committee have no effect on financial performance. Based on the results of the simultaneous test, it shows that the independent board of commissioners, managerial ownership, institutional ownership, and audit committee have an effect on the dependent variable of financial performance. Keywords: Financial Performance, Good Corporate Governance